GEODIVERSITY GUNUNG API JABOI KOTA SABANG - Tesalonika, Tesalonika; Ramadanika, Ramadanika; Imam, Muhammad; Silalahi, Enjelina Tiurma Br.; Nanda, Nur Rahma; Syafira, Amelia (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
Reviewing the geological diversity (geodiversity) in an area is important to review as a candidate for a geopark area. Jaboi Volcano located on Sabang Island is a type C volcano that shows volcanic activity in the form of a mud crater and sulfur in it, Sabang Island which was formed because of the volcanic activity of Mount Seulawah is related to the presence of the Jaboi Volcano type C which is located on the coastal island. Jaboi volcano is one form of type C volcano as evidenced by traces of fulmora volcanic activity left by volcanic activity. As well as the existing crater holes, and the trees growing on the mountain die because of the heat from the sulfur holes that continue to grow and move so that it is possible that the sulfur holes and crater holes can move to the next hill near the mountain at any time.